The Role of Truck Art in Sustaining Indigenous Artistic Traditions in Pakistan - Jahanzaib Afridi; Hadia Saleem (Indus Journal of Social Sciences, 2025)
This research investigated how truck art maintains native artistic customs in Khyber Pakhtunkhwa (KPK). The study analyzed truck art by using visual analysis as the main approach to investigate its cultural functions including identity maintenance and social commentary and cultural expression. The evaluation revealed cultural symbolism and identity as its first theme while religious and spiritual expression followed as the second theme before national pride and political messages emerged as the third theme and emotional and social commentary served as the fourth theme. Every theme within the study showcased how truck art develops its distinctive bond with local cultural communities while sustaining their traditional and religious principles. The comprehensive study illustrated how truck art functions as a powerful visual communication tool because of its colorfulness and inscription poetry as well as its animal designs and religious visual language. The study findings received backing from fieldwork photographs that showed the extensive diversity of this artistic tradition. Truck art acts as a primary preserver and transmitter of indigenous heritage which delivers dual aesthetic and cultural importance in a society that experiences modernization.